2018
DOI: 10.1103/revmodphys.90.025006
|View full text |Cite
|
Sign up to set email alerts
|

Looking at cosmic near-infrared background radiation anisotropies

Abstract: The cosmic infrared background (CIB) contains emissions accumulated over the entire history of the Universe, including from objects inaccessible to individual telescopic studies. The near-IR (∼ 1 − 10 µm) part of the CIB, and its fluctuations, reflects emissions from nucleosynthetic sources and gravitationally accreting black holes (BHs). If known galaxies are removed to sufficient depths the source-subtracted CIB fluctuations at near-IR can reveal sources present in the first-stars-era and possibly new stella… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 421 publications
(591 reference statements)
1
77
0
Order By: Relevance
“…The source-subtracted CIB fluctuations could be contributed by the shot noise from remaining sources in the beam, and the clustering of the remaining CIB sources. The CIB fluctuations are measured at a given shot noise level, P SN = S 2 (m)dN(m), which we express in units of nJy nW m −2 sr −1 (see Kashlinsky et al 2018, Sect IV.A.1). The COSMOS maps are clipped to the shot noise level of ∼86 nJy nW m −2 sr −1 and other maps are at the level of ∼50 and ∼30 nJy nW m −2 sr −1 in 3.6 and 4.5 µm, respectively.…”
Section: Spitzer Ir Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The source-subtracted CIB fluctuations could be contributed by the shot noise from remaining sources in the beam, and the clustering of the remaining CIB sources. The CIB fluctuations are measured at a given shot noise level, P SN = S 2 (m)dN(m), which we express in units of nJy nW m −2 sr −1 (see Kashlinsky et al 2018, Sect IV.A.1). The COSMOS maps are clipped to the shot noise level of ∼86 nJy nW m −2 sr −1 and other maps are at the level of ∼50 and ∼30 nJy nW m −2 sr −1 in 3.6 and 4.5 µm, respectively.…”
Section: Spitzer Ir Datamentioning
confidence: 99%
“…Following these theoretical proposals, Kashlinsky et al (2005Kashlinsky et al ( , 2007 identified in deep Spitzer-based analysis significant source-subtracted CIB fluctuations at levels much higher than expected from remaining known sources Helgason et al 2012Helgason et al , 2014. See the recent review by Kashlinsky et al (2018) for summary and discussion.…”
mentioning
confidence: 95%
“…Using Spitzer data, Kashlinsky et al (2012) find marginal cross-correlations with the NIR and 8 micron emission, while Matsumoto et al (2011) find no cross-correlation with longer wavelength 100 micron maps with AKARI. In contrast, Thacker et al (2015) do report a cross-correlation at longer 250, 350, and 500 micron wavelengths, but Kashlinsky et al (2018) argues that the claimed signal may be derived from known Galactic populations. At the shorter wavelengths probed by HST, Mitchell-Wynne et al (2015) observe a clear power-law on scales > 1 , which they attribute to diffuse Galactic light.…”
Section: Are We Missing a Galactic Foreground?mentioning
confidence: 92%
“…Observationally, it has been difficult to estimate the contribution from Galactic cirrus to the NIR fluctuations, as discussed in detail in Kashlinsky et al (2018). The main method with which to assess its contribution has been to attempt to find cross-correlations with bands where cirrus is known to be dominant.…”
Section: Are We Missing a Galactic Foreground?mentioning
confidence: 99%
See 1 more Smart Citation